#TITLE_ALTERNATIVE# - MOHAMAD FAUZI RAMDHAN (NIM: 10312032), RADEN
B-emission (Be) stars are B-type stars class with luminosity III Ã‚Â– V, rotate very fast and show the emission profile of the hydrogen Balmer line, especially Hα. The existence of emission lines in the visual region, shows that here is a cold envelope around the starÃ‚Â’s equator. Observations in the UV region indicate the presence of high ionized elements, such as Si IV, C IV, Al III in the polar regions, as the hot envelope. Be star EW Lac (HR8731 / HD217050) shows V / R (violet to red) variability with high intensity of Hα emissions during a certain time interval. Using the model of one-armed oscillation, it is found that the profile of V / R is generated by a region in the cold envelope, moves with opposite direction to the rotation of the star (retrograde). Based on the analysis of observational data in the UV region, it shows that there is a part of the hot envelope of EW Lac trapped in the cold envelope and follows the rotating sheath against the main star.